Zasada równości w prawie i procesie karnym Republiki Federalnej Niemiec: [The principle of equality in law and criminal proceedings in the Federal Republic of Germany] (Studia Prawnicze / The Legal Studies, 1983)
The article presents the problems of equality before law in substantive criminal law and law of criminal proceedings in the Federal Republic of Germany. The principle of equality before law is in the legal system of the Federal Republic of Germany a constitutional principle addressed to and binding for all state authorities, thus both for law-making and law-enforcing agencies. It means that an individual (a citizen) has a right to be treated by state authorities in such a way that principle of equality is not violated.In the field of penal law the problem of equality refers to the following questions, enumerated in the article. To the question of meting out punishment by the court where the principle of equality may seem to be in conflict with the principle of independence of the judiciary. In this respect the realization of the principle of equality is supervised by courts of appeal. The above mentioned principle may be realized by the system of meting out a fine which has been applied for a few years.In the field of rules of procedure the problem of equality emerges, first of all, in case of guaranteeing equality to the parties to the proceedings, \which is connected with all rules of procedure and the model of criminal proceedings. The problem of guaranteeing the right to formal defence (to have a counsel for the defence) and, in particular, the institute of necessary defence and legal assistance for indigent persons is very important.In the field of application of criminal law the most important problems occur in relation to the position of foreigners in the proceedings who do not know the German language and to the treatment by prosecution organs of people belonging to various social classes.